PENGARUH HARGA, INOVASI PRODUK, DAN MEDIA SOSIAL TERHADAP KEPUTUSAN PEMBELIAN VIVI JILBAB DI KOTA JAMBI - Lia Rahmasari; Mellya Embun Baining; Erwin Saputra Siregar (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This research aims to determine the influence of price, product innovation, social media on consumer purchasing decisions for Vivi Jilbab in Jambi City. This research uses a quantitative approach and the data analysis method used is multiple linear regression. The sampling technique used purposive sampling as many as 97 respondents who were distributed to Vivi Jilbab consumers. The research results show that price partially has a positive and significant effect on purchasing decisions with the results Tcount > Ttable (2.086 > 1.66140) and significance (0.040 < 0.05), product innovation partially has a positive and significant effect on purchasing decisions with the results Tcount > Ttable (2.316 > 1.66140) and significance (0.030 < 0.05), social media partially influences the decision to purchase Vivi Jilbab with the results Tcount > Ttable (2.193 > 1.66140) and significance is (0.031 < 0.05 ). Based on the price F test, product innovation and social media simultaneously influence purchasing decisions with the results Fcount > Ftable (4.592 > 2.70) and significance (0.005 < 0.05). The adjusted R square value obtained is 0.846 or it could be said that 84.6% of purchasing decision variables are influenced by price variables, product innovation and social media. Meanwhile, the remaining 15.4% was influenced by other variables not examined in this research